Embedding quantitative principles in life science education. - Adams, Peter; Poronnik, Philip (Australian Learning and Teaching Council, 2010)
There is a well-documented flight from science highlighted by a significant reduction in the numbers of students taking the enabling sciences, particularly mathematics. One of the more alarming but less well-documented consequences of this fright of numbers is that the basic mathematical and quantitative skills of many students in the life sciences is below the level required for the quantitative data acquisition and analysis that underpins fundamental scientific activity, education and research. The purpose of this report is to quantify the extent of the mathematical deficiency in first year life science students and to develop interventions to address these deficiencies. -- p. 3